Tribiotication strategy for the functionalization of bovine colostrum through the biochemical activities of artisanal and selected starter cultures. Issue 1 (1st January 2020) - Cotârleţ, Mihaela; Vasile, Aida Mihaela; Gaspar-Pintiliescu, Alexandra; Oancea, Anca; Bahrim, Gabriela Elena
ABSTRACT: The main aim of this study was to transform bovine colostrum into a tribiotic product through a metabolic conversion with a microbial consortium based on artisanal and starter microorganisms. As such, the bovine colostrum was firstly transformed enzymatically for 48 h with a selected strain of a non-pathogenic Candida lipolytica strain, and then lactic acid fermentation was performed for 48 h, by using a co-culture of 25 g/L fresh kefir grains and a 10 g/L commercial FreshQ ® culture (Chr. Hansen, Denmark). The obtained product is recommended to be used as an ingredient for the milk-derived nutraceuticals' formulation. As such, the product displayed increased antioxidant potential of 3.15 mM Trolox equivalent/g. Furthermore, the peptide fractions with a molecular weight lower than 3 kDa showed a notable in vitro ABTS radical scavenging activity, similar to a concentration of 2 nM captopril, hence proving a high potential in reducing the blood pressure.